POPULATION DENSITY AND HABITAT STATUS OF PUNJAB URIAL (Ovis vignei punjabiensis) IN DILJABBA-DOMELI GAME RESERVE, PUNJAB PAKISTAN - U. Habiba; M. Anwar; I. Hussain; M. Rais (Journal of Animal and Plant Sciences, 2015)
Present study provides information on population and habitat status of the Punjab urial (Ovis vignei punjabiensis) in Diljabba-Domeli Game Reserve located in District Jhelum. Data regarding population density of urial was collated through direct observations using line transects and vegetation survey of the study area using the quadrat method. A total of 51 urials; 37 females (30 adult, 7 young) and 14 males, were recorded. The urial population density was  estimated at 2.68 animals/km2. Population density varied among four transects/study sites but largely remained non-significant. Occurrence of the Punjab urial was found between 330m and 600m elevation in the reserve, and predominant plant species in its habitat were Acacia modesta, Capparis aphylla, Ziziphus nummularia, Prosopis glandulosa, Adhatoda zeylanica, Sageretia theezans, Maytenus royleana, Dodonea viscosa, Grewia tenax, Lantana camara, Cynodon dactylon, Sonchus arvensis and Suaeda fruticosa. Types of grasses found here ranged to about 31.25%. Terrain comprised of foothills with medium gentle slopes, mixed with flat plain areas, and also the gravels and boulders. Major threats to the urial population included a rapid decline in their present habitat, poaching, competition with livestock, habitat fragmentation, scarcity of water during summer season and capture of urial lambs which are largely kept as pet. Therefore, it seems pertinent for the wildlife managers to maintain and enforce wildlife laws for conservation of Punjab urial and its habitat in the reserve.
Keywords: Punjab urial; population density; habitat use; threats; habitat loss; hunting